Horizontal Gene Transfer of Fluoroquinolone Resistance-Conferring Genes From Commensal Neisseria to Neisseria gonorrhoeae: A Global Phylogenetic Analysis of 20,047 Isolates - Manoharan-Basil, Sheeba Santhini; González, Natalia; Laumen, Jolein Gyonne Elise; Kenyon, Chris (Frontiers in Microbiology, 2022)
Antimicrobial resistance in Neisseria gonorrhoeae is an important global health concern. The genetically related commensal Neisseria act as a reservoir of resistance genes, and horizontal gene transfer (HGT) has been shown to play an important role in the genesis of resistance to cephalosporins and macrolides in N. gonorrhoeae. In this study, we evaluated if there was evidence of HGT in the genes gyrA/gyrB and parC/parE responsible for fluoroquinolone resistance. Even though the role of gyrB and parE in quinolone-resistance is unclear, the subunits gyrB and parE were included as zoliflodacin, a promising new drug to treat N. gonorrhoeae targets the gyrB subunit. We analyzed a collection of 20,047 isolates; 18,800 N. gonorrhoeae, 1,238 commensal Neisseria spp. and 9 Neisseria meningitidis. Comparative genomic analyses identified HGT events in genes, gyrA, gyrB, parC and parE. Recombination events were predicted in N. gonorrhoeae, and Neisseria commensals. N. lactamica, N. macacae and N. mucosa were identified as likely progenitors of the HGT events in gyrA, gyrB and parE, respectively.